2021
DOI: 10.1021/acsphotonics.1c01149
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Polymer Photonic Films with Embedded Microvoids for High-Performance Passive Daytime Radiative Cooling

Abstract: Passive radiative cooling, a promising strategy for energy savings and sustainability, enables cooling of the ambient temperature by synchronously reflecting sunlight and dissipating heat to the ultracold outer space through the atmospheric transparency window. While designed photonic structures have shown intriguing passive radiative cooling performance, the implementation of such photonic radiators remains challenging due to complex nanoscale lithography/synthesis and rigidity. Here, we experimentally demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 42 publications
0
39
0
Order By: Relevance
“…Passive radiative cooling polymer coatings (PRCPCs) represent one of the most facile and efficient energy-saving strategies for controlling spacing temperature. They usually have heterogeneous micro/nanostructures that reflect solar light (wavelength range of 0.3–2.5 μm) but allow for thermal emission to the cold outer space through the atmospheric longwave infrared (LWIR) transparent window (wavelength: 8–13 μm) . Such heterogeneous structures can be created by introducing cavities or particles into the polymer matrices. ,, This idea has inspired the design of various PRCPCs with excellent cooling performance. When great attention is focused on improving the coating’s cooling performance, many other aspects should also be considered for practical applications of these coatings. One aspect is the combination of additional desirable functions.…”
Section: Introductionmentioning
confidence: 99%
“…Passive radiative cooling polymer coatings (PRCPCs) represent one of the most facile and efficient energy-saving strategies for controlling spacing temperature. They usually have heterogeneous micro/nanostructures that reflect solar light (wavelength range of 0.3–2.5 μm) but allow for thermal emission to the cold outer space through the atmospheric longwave infrared (LWIR) transparent window (wavelength: 8–13 μm) . Such heterogeneous structures can be created by introducing cavities or particles into the polymer matrices. ,, This idea has inspired the design of various PRCPCs with excellent cooling performance. When great attention is focused on improving the coating’s cooling performance, many other aspects should also be considered for practical applications of these coatings. One aspect is the combination of additional desirable functions.…”
Section: Introductionmentioning
confidence: 99%
“…The optical properties of PMMA are discussed in this section before and after pore-forming. The extinction coefficient ( k ) is an important parameter that reflects the emission performance of the material in the infrared spectral band. , The reflection index ( n ) and extinction coefficient ( k ) are both shown in Figure a,b, respectively, based on refs and. It was shown that the multiple extinction peaks of PMMA were found in the transparent window band of the atmosphere.…”
Section: Resultsmentioning
confidence: 99%
“…Gentle and Smith have done great work in radiative cooling through paints since the 1990s and silver under-layers from 2015. In 2017, the Yang group completed a pioneering work in the application of radiative cooling technology using a metamaterial created from resonance polar dielectric microbeads (SiO 2 ) embedded in the organic polymer polymethylpentene (TPX) and realized the large-scale roll-to-roll manufacturing . The metamaterial showed an infrared emissivity of greater than 0.93, a reflectance of more than 0.96 with the assistance of a silver coating, and a noontime radiative cooling power of 93 W/m 2 under direct sunshine. Hierarchically porous polymer coatings with enhanced backscattering of sunlight have been illustrated with superior radiative cooling performance. Moreover, the raw materials can be further lower in the market prices, and the application prospect will be even broader.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Zhou et al developed the flexible photonic films with uniform porous structure (3D microvoid arrays) through homogeneous polystyrene microsphere embedding into PDMS films. [82] With the controllable porous structure, the structural polymer can endow the solar reflectivity of ≈93.4% and infrared emissivity of ≈94.6%, resulting in a temperature drop of ≈5.8 K under direct solar radiation (Figure 5d-f). More importantly, the uniform and close-packed microsphere template offered a facile and well-suited pathway toward the low-cost and highperformance porous photonic structures.…”
Section: Medium Embedding-extracting Methodsmentioning
confidence: 99%
“…Copyright 2021, Springer Nature. d-f) Reproduced with permission [82]. Copyright 2022, American Chemical Society.…”
mentioning
confidence: 99%